Neuroprotective effects of resveratrol and epigallocatechin gallate polyphenols are mediated by the activation of protein kinase C gamma - Menard, Caroline; Bastianetto, Stephane; Quirion, Remi (Frontiers in Cellular Neuroscience, 2013)
Polyphenols such as epigallocatechin gallate (EGCG) and resveratrol have received a great deal of attention because they may contribute to the purported neuroprotective action of the regular consumption of green tea and red wine. Many studies, including those published by our group, suggest that this protective action includes their abilities to prevent the neurotoxic effects of beta-amyloid, a protein whose accumulation likely plays a pivotal role in Alzheimer’s disease. Moreover, the scavenging activities of polyphenols on reactive oxygen species and their inhibitory action of cyclooxygenase likely explain, at least in part, their antioxidant and anti-inflammatory activities. Besides these well-documented properties, the modulatory action of these polyphenols on intracellular signaling pathways related to cell death/survival (e.g. protein kinase C, PKC) has yet to be investigated in detail. Using rat hippocampal neuronal cells, we aimed to investigate here the effects of EGCG and resveratrol on cell death induced by GF 109203X, a selective inhibitor of PKC. The MTT/resazurin and spectrin assays indicated that EGCG and resveratrol protected against GF 109203X-induced cell death and cytoskeleton degeneration, with a maximal effect at 1 and 3 µM, respectively. Moreover, immunofluorescence data revealed that cells treated with these polyphenols increased PKC gamma (g) activation and promoted neuronal interconnections. Finally, we found that the protective effects of both polyphenols on the cytoskeleton and synaptic plasticity were mediated by the PKCg subunit. Taken together, the results suggest that PKC, and more specifically its g subunit, plays a critical role in the protective action of EGCG and resveratrol on neuronal integrity.